2022
DOI: 10.7759/cureus.21524
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Abruptio Placenta in Women With Pregnancy-Induced Hypertension

Abstract: Background: Bleeding that takes place after premature separation of the normally situated placenta, usually after 20 weeks of pregnancy, is known as abruptio placenta. Factors increasing chances of abruptio placenta are advanced age pregnancy, parity, smoking, pregnancy-induced hypertension, pre-eclampsia, and previous incidence of abruptio. The objective of the study was to find the frequency of abruptio placenta in women with pregnancy-induced hypertension. Methods: This descriptive prospective st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Four cases (4%) were nulliparous, whereas 53 patients (51,9%) had parity of two or above. Median value with minimum and maximum values of patients' parities was and Asian populations (4,(17)(18)(19). The higher incidence of AP in our study may be due to the fact that our hospital is a tertiary referral public hospital with its high patient capacity.…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…Four cases (4%) were nulliparous, whereas 53 patients (51,9%) had parity of two or above. Median value with minimum and maximum values of patients' parities was and Asian populations (4,(17)(18)(19). The higher incidence of AP in our study may be due to the fact that our hospital is a tertiary referral public hospital with its high patient capacity.…”
Section: Resultsmentioning
confidence: 63%
“…The concealed type is considerably hazardous due to the blood loss level does not correspond with maternal heart rate and blood pressure and is concluded to have more fetal death in comparison to the revealed type as well (5). Predisposing factors for abruptio placenta comprise hypertensive disorders of pregnancy, multiparity, being under the age of 20, advanced maternal age which is above 35, formerly having abruptio placenta, uterine anomalies, multiple pregnancy, polyhydramnios, smoking, cocaine use, blunt abdominal trauma, retroplacental leiomyoma, premature rupture of membranes, thrombophilic disorders, and short umbilical cord (4). The clinical signs depend on the degree of placental detachment and bleeding amount.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 One recent study found a strong association between placental abruption and hypertension (defined as  140/90 mmHg) in pregnant women after 20 weeks gestation. 38 Our findings suggest that even mild BP elevations after 20 weeks gestation may severely impact maternal and neonatal morbidity and mortality. However, there is much unknown about the association between placental abruption and hypertension, as defined by the ACC/AHA, after 20 weeks gestation.…”
Section: Accepted Manuscriptmentioning
confidence: 67%
“…11 In our study, 4/34 i.e 11.76 % women with hypertensive disorder of pregnancy had placental abruption where as Saba et al found it in 29.4% cases of hypertensive disorder of pregnancy. 19 Lower frequency of placental abruption in our hypertensive patients could be due to differences in social and demographic variables of the two study groups and better antenatal care services provided to our patients.…”
Section: Discussionmentioning
confidence: 83%